MxA suppresses TAK1-IKKα/β-NF-κB mediated inflammatory cytokine production to facilitate Mycobacterium tuberculosis infection. Issue 2 (August 2020) - Zhou, Xinying; Zhang, Lijie; Lie, Linmiao; Zhang, Zelin; Zhu, Bo; Yang, Jiahui; Gao, Yuchi; Li, Pengfei; Huang, Yingqi; Xu, Hui; Li, Yanfen; Du, Xialin; et al.
Highlights: Mtb infection induced MxA expression to promote intracellular Mtb infection in Mφs. MxA silencing promoted inflammatory cytokines IL-1β, IL-6 and TNF-α production. MxA silencing promoted TAK1-IKKα/β-NF-κB signaling pathway activation. Summary: Objectives: Interferons (IFNs) play multifunctional roles in host defense against infectious diseases by inducing IFN-stimulated genes (ISGs). However, little is known about how ISGs regulate host immune response to Mycobacterium tuberculosis (Mtb) infection, the major cause of tuberculosis (TB). Methods: We thus profiled the potential effects and mechanisms of eight Mtb-induced ISGs on Mtb infection by RNA interference in human macrophages (Mφs) derived from peripheral blood monocytes (hMDMs) and THP-1 cell line derived Mφs (THP-1-Mφs). Results: MxA silencing significantly decreased intracellular Mtb infection in Mφs. Mechanistically, MxA silencing promoted inflammatory cytokines IL-1β, IL-6 and TNF-α production, and induced NF-κB p65 activation. Pharmacological inhibition of NF-κB p65 activation or gene silencing of NF-κB p65 blocked the increased production of IL-1β, IL-6 and TNF-α and restored Mtb infection by MxA silencing. Furthermore, pharmacological inhibition of TAK1 and IKKα/β blocked NF-κB p65 activation and subsequent production of pro-inflammatory cytokines by MxA silencing. Isoniazid (INH) treatment and MxA silencing could promote TAK1-IKKα/β-NF-κB signaling pathway activation and combat Mtb infection independently. Conclusions: Our results reveal a novel role of MxA in regulating TAK1-IKKα/β-NF-κB signaling activation and production of antimicrobial inflammatory cytokines upon Mtb infection, providing a potential target for clinical treatment of TB. Graphical abstract: MxA silencing significantly decreased intracellular Mtb infection in Mφs. Mechanistically, MxA silencing promoted inflammatory cytokines IL-1β, IL-6 and TNF-α production, and induced NF-κB p65 activation. Pharmacological inhibition of NF-κB p65 activation or gene silencing of NF-κB p65 blocked the increased production of IL-1β, IL-6 and TNF-α and restored Mtb infection by MxA silencing. Furthermore, pharmacological inhibition of TAK1 and IKKα/β blocked NF-κB p65 activation and subsequent production of pro-inflammatory cytokines by MxA silencing. Image, graphical abstract